A BIPOTENTIOMETRIC FIA SYSTEM FOR DETERMINATION OF VITAMIN C - ., Harjana; Siswanto, Imam; ., Muzakki; ., Sumardi; Huda, Miftahul (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
A bipotentiometric FIA system has been developed for the determination of vitamin C. The systemÂ was a single stream manifold, which consisted of a peristaltic pump, a self made injector with internal loop and two Pt-electrodes connected to a PC by serial ADC or parallel ADC interface card. One of the Ptelectrodes was located in the injector before the internal loop, while the other electrodes at the end of the TEFLON reaction tube. The PC was supported with a self-made software for controlling the pump, signal acquisition, processing, and visualisation, and further peak determination, followed by calibration of standard solutions and calculation of sample concentrations. The above FIA-system configuration was applied to determine vitamin C by the injection of sample solution into a stream of potassium hexacyanoferrate (III) solution. The optimum result was achieved with knitted tube reaction of 0.8 mm i.d., 50 cm length, at flow rate 0,64 ml/minute, and consumed 3.6 ml of carrier solution per five injection, and gave linearity range at 0.001 â€“ 0.100 N vitamin C, with the coefficient of correlation 0.9999, RSD peak to peak better than 3.0% and the error of artificial samples were less than 3.4 %.Key Words : Bipotentiometric-FIA, injector with internal loop, module-program, vitamin C